Analisis Dan Perancangan Sistem Penunjang Keputusan Pemilihan Program Studi Pada Universitas Adiwangsa Jambi - Iswanti, Dewi Nur; Sarjono, Sarjono (LPPM Universitas Dinamika Bangsa, 2020)
Adiwangsa Jambi University, is a change in form and an increase in status of Stikes Prima Jambi.Adiwangsa Jambi University (UNAJA) located on St. Sergeant Muslim RT. 24 Coffee Plantation Exit ThehokSouth Jambi Jambi City. Has 5 faculties including the Faculty of Health & Pharmacy, Faculty ofEngineering & Computer Science, Teacher Training & Education Faculty, Faculty of Economics, andFaculty of Law. some new students who register are still confused with the choice of concentration of studyprograms at Adiwangsa University Jambi. Errors in the selection of this study program will have anunfavorable impact when the student follows a course that is taught, among others, understanding thematerial and there are also less capable of the subjects he took. To overcome these problems researchersconduct research with the aim of designing a prototype system to support the selection of study programsthat will later solve existing problems.